2021
DOI: 10.1080/03054985.2020.1862779
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination against Dutch Muslim youths in the school context and its relation with externalising behaviour

Abstract: The role of the source of discrimination in relation to minority Muslim youths' psychosocial well-being has received remarkably little attention in the post-9/11 climate. We have examined one of the aspects of psychosocial well-being that is given prominent attention in the media and public discourse, namely externalising behaviour. The article reports whether perceived discrimination by four sources (school peers and teachers, peers, and adults outside the school) is related to externalising behaviour. Links … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Beyond academics, discriminatory experiences can influence externalizing behaviors among adolescents including aggression, substance abuse, and disobedience (Benner et al., 2018). For instance, Dutch Muslim youth who reported incidents of discrimination by their teachers were more likely to exhibit externalizing behaviors like lying, stealing, and aggression (van Bergen et al., 2021). These findings highlight the broad impact of discriminatory experiences on various aspects of Muslim students' academic and behavioral outcomes.…”
Section: The Consequences Of Islamophobia and Stigmamentioning
confidence: 99%
“…Beyond academics, discriminatory experiences can influence externalizing behaviors among adolescents including aggression, substance abuse, and disobedience (Benner et al., 2018). For instance, Dutch Muslim youth who reported incidents of discrimination by their teachers were more likely to exhibit externalizing behaviors like lying, stealing, and aggression (van Bergen et al., 2021). These findings highlight the broad impact of discriminatory experiences on various aspects of Muslim students' academic and behavioral outcomes.…”
Section: The Consequences Of Islamophobia and Stigmamentioning
confidence: 99%
“…Specifying the source of discrimination is important. A study in the Netherlands found that only teacher discrimination (and not peer or adults outside of school) was linked to externalizing behaviour among Muslim Dutch adolescents (van Bergen, Feddes, & de Ruyter, 2021). Studies in the U.S. find that the source of discrimination may vary by ethnic‐racial group and have differential consequences.…”
Section: What Do We Know and What Areas Are Understudied?mentioning
confidence: 99%